Immune Checkpoint Inhibitors in Tumors Harboring Homologous Recombination Deficiency: Challenges in Attaining Efficacy - Silva, Saulo Brito; Wanderley, Carlos Wagner S.; Colli, Leandro Machado (Frontiers in Immunology, 2022)
Cancer cells harbor genomic instability due to accumulated DNA damage, one of the cancer hallmarks. At least five major DNA Damage Repair (DDR) pathways are recognized to repair DNA damages during different stages of the cell cycle, comprehending base excision repair (BER), nucleotide excision repair (NER), mismatch repair (MMR), homologous recombination (HR), and non-homologous end joining (NHEJ). The unprecedented benefits achieved with immunological checkpoint inhibitors (ICIs) in tumors with mismatch repair deficiency (dMMR) have prompted efforts to extend this efficacy to tumors with HR deficiency (HRD), which are greatly sensitive to chemotherapy or PARP inhibitors, and also considered highly immunogenic. However, an in-depth understanding of HRD’s molecular underpinnings has pointed to essential singularities that might impact ICIs sensitivity. Here we address the main molecular aspects of HRD that underlie a differential profile of efficacy and resistance to the treatment with ICIs compared to other DDR deficiencies.